2020
DOI: 10.1051/0004-6361/201936540
|View full text |Cite
|
Sign up to set email alerts
|

NGC 6240: A triple nucleus system in the advanced or final state of merging

Abstract: Aims. NGC 6240 is a well-studied nearby galaxy system in the process of merging. Based on optical, X-ray, and radio observations, it is thought to harbor two active nuclei. We carried out a detailed optical 3D spectroscopic study to investigate the inner region of this system in connection with existing MERLIN and VLBA data. Methods. We observed NGC 6240 with very high spatial resolution using the MUSE instrument in the Narrow-Field Mode with the four-laser GALACSI adaptive optics system on the ESO VLT under s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 59 publications
(68 reference statements)
3
53
1
Order By: Relevance
“…The nuclei are at ∼ 1 kpc separation and are likely both Compton thick (i.e., with absorption column density along the line of sight N H > ∼ 10 24 cm −2 ). Recently, Kollatschny et al (2019), using VLT/MUSE data at a resolution of 75 milliarcsec, have reported the discovery of a third nucleus in this galaxy: the Southern component appears to host two distinct nuclei, separated by 198 pc only. The lack of a radio counterpart for the newly detected nucleus suggests that it could be not active; furthermore, no 12 CO(2-1) emission at its position is detected by ALMA (Treister et al, 2020), in stark contrast with the two previously known nuclei.…”
Section: Discovery and Follow-up Observations Of Dual Agnmentioning
confidence: 99%
“…The nuclei are at ∼ 1 kpc separation and are likely both Compton thick (i.e., with absorption column density along the line of sight N H > ∼ 10 24 cm −2 ). Recently, Kollatschny et al (2019), using VLT/MUSE data at a resolution of 75 milliarcsec, have reported the discovery of a third nucleus in this galaxy: the Southern component appears to host two distinct nuclei, separated by 198 pc only. The lack of a radio counterpart for the newly detected nucleus suggests that it could be not active; furthermore, no 12 CO(2-1) emission at its position is detected by ALMA (Treister et al, 2020), in stark contrast with the two previously known nuclei.…”
Section: Discovery and Follow-up Observations Of Dual Agnmentioning
confidence: 99%
“…Assuming a Hubble constant of H 0 = 68 km s −1 Mpc −1 (Planck Collaboration et al 2014) at the distance of NGC 6240 1 ′′ corresponds to 500 pc, respectively the cores settle on 750 pc. Kollatschny et al (2020) reported a third minor component S2 which placed at 0.42 ′′ (210 pc) from S1 (previous S) nuclei. Below for marking south nu-cleus we will use label S (S1+S2) if we talk about binary system or S1/S2 if we talk about triple system.…”
Section: Ngc 6240 Physical Characteristicsmentioning
confidence: 89%
“…With its 27 Mpc in distance, NGC 7727 is the dual SMBH system closest to us. Before this work, the closest known dual SMBH was NGC 6240 (Komossa et al 2003;Kollatschny et al 2020), which at 144 Mpc is almost six times as far away from us as NGC 7727. In NGC 6240, similar MUSE data were used to study the system, but only the nuclear components could be spatially separated from each other.…”
Section: The Nearest and Closest Dynamically Confirmed Dual Smbh Systemmentioning
confidence: 99%
“…The closest known dual SMBH is NGC6240 (Komossa et al 2003;Kollatschny et al 2020), which is located at 144 Mpc. In the study of NGC 6240 by Kollatschny et al (2020), based on MUSE observations, a spatial resolution was reached that is good enough to show that the emission lines come from two separate stellar components and are thus a true dual SMBH. They discovered that it might be a triple AGN system with three accreting black holes within a separation of ∼1 kpc.…”
Section: Introductionmentioning
confidence: 99%